THE IMPACT OF PHYSICAL EDUCATION CLASSES ON THE PSYCHOLOGICAL AND EMOTIONAL WELL-BEING OF STUDENTS OF HIGHER EDUCATION INSTITUTIONS - Prokhorenko A.A.; Antonov A.V.; Rukavishnikova S.K. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to determine the degree of influence of classes in the discipline "Physical Education" on the psycho-emotional state of students. Methods and structure of the study. The analysis of the psycho-emotional state of students was carried out in three directions. The first direction is a comparison of the results of the SAN test during the training process (after practical classes) with the period without classes. The second direction is during the training process: 2 hours before the practical class and after 1 hour after the class. The third direction is a comparison of indicators during the training process (2 hours before the class) with the indicators of the period without classes. Results and conclusions. Most students consider practical classes in the discipline "Physical Education" to have a positive effect on their psycho-emotional state. The results of the study confirmed that classes in the discipline "Physical Education" are an important factor in improving the psycho-emotional state of students.